Explaining the 25-year decline of serum cholesterol by dietary changes and use of lipid-lowering medication in Finland - Valsta, Liisa M; Tapanainen, Heli; Sundvall, Jouko; Laatikainen, Tiina; Männistö, Satu; Pietinen, Pirjo; Vartiainen, Erkki (Public health nutrition, 2010)
To assess to what extent the observed dietary changes and increased use of lipid-lowering medication can explain the almost 20 % decline in serum cholesterol (referring to serum total cholesterol) level observed from 1982 to 2007 in Finland. Predicted changes of serum cholesterol were calculated by the Keys' equation assuming the effect of trans fatty acids to be similar to SFA and using the dietary intake data of the national dietary surveys between 1982 and 2007. The effect of medication was estimated based on the information on use of lipid-lowering medication among survey participants. The predicted serum cholesterol levels were compared with observed changes in analysed serum cholesterol levels. Four cross-sectional population surveys, in 1982, 1992, 2002 and 2007, in the provinces of North Karelia, Northern Savo and Southwestern Finland. A total of 2325 men and 2638 women aged 26-64 years selected randomly from the national population register for the four surveys. Changes in dietary fat quality and cholesterol intake explain 0.70 mmol/l (65 %) of the decrease in men and 0.65 mmol/l (60 %) of the decrease in women in all subjects. Decline in dietary SFA intake is the main explanatory factor (47 % in men and 41 % in women) for the changes. The impact of lipid-lowering medication on observed cholesterol levels was found to be 16 % among men and 7 % among women. The decrease in serum cholesterol levels in Finland can be explained mainly by dietary changes, especially changes in fat quality. The effect of lipid-lowering medication is less significant.